The Implementation of Project-Based Learning With Integrated STEM in Distance Learning - Baihaqi, Muhammad Arifin; Sarwi, Sarwi; Ellianawati, Ellianawati (Educational Management, 2020)
This study aimed to analyze the improvement of communication skills through project-based learning with integrated STEM in distance learning. The research method was a type of quantitative experiment using Pre-Test Post-Test in one group. The research sample was fifth grade students from A-Elementary School, B-Elementary School, C-Elementary School, D-Elementary School in Magelang City with a total of 78 students. Data obtained through tests collected on google forms. Communication skills were analyzed using the N-gain test. The relationship between written and oral communication was analyzed using the correlation test. Final results showed that the ability of oral and written communication increased by an average of 0.67 and 0.57 with the moderate category. The results of the N-gain showed that project-based learning with integrated STEM can improve oral and written communication of each student in the moderate category. The relationship between collaboration and communication skills showed a positive direction, which mean that the better oral communication skills, the better written communication skills will be